Purchasing Decision of Gen Z Reviewed by Viral Marketing and Food Quality in Noodle’s Restaurant - Susilawati, Erna; Pratama, M Ridho Rizki (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2024)
Gen Z as the generations who known as technology literate, and they intend to stay with gadget and internet. Because of that, everything that viral on internet got their interest and became their reference for their purchasing decisions. This research aims to know is there any effect of viral marketing and food quality on purchasing decisions of Gen Z in Gacoan Restaurant Bandung both partially and simultaneously. This research used quantitative method and the data processed using SPSS program. The respondents of research are 100 customers of Gacoan Restaurant in Bandung. The result shows there is positive effect of Viral marketing and Food Quality on Purchasing Decisions of Gen Z both partially and Simultaneously